Pemenuhan Nafkah Iddah dalam Perundangan Islam: Hak Perempuan Pasca Perceraian - Laili Hidayatul Maghfiroh; Nur Faizah (MASADIR: Jurnal Hukum Islam, 2024)
This study reveals several important aspects related to iddah maintenance for women in Mojopuro Wetan Village. First of all, it is seen that the understanding and practice of iddah maintenance are influenced by strong cultural factors in the community. Patriarchal culture and existing social norms often limit women's access to their iddah maintenance, both in terms of economy and decision-making.In addition, the role of religion in the concept of iddah maintenance is also very important. However, the fact that occurs in society is that ex-husbands do not provide maintenance for their children and ex-wives.In addition, economic and educational factors also play a major role in the understanding and implementation of iddah maintenance. Even though they are educated and have demanded their children's maintenance rights but are not given, they finally decide to work to meet the needs of their children